2022
DOI: 10.1155/2022/8966920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Additional Mirror Therapy on the Recovery of Upper Extremity Motor Function after Stroke: A Single-Blind, Randomized Controlled Trial

Abstract: Background. Rehabilitation of upper extremity hemiplegia after stroke remains a great clinical challenge, with only 20% of patients achieving a basic return to normal hand function. How to promote the recovery of motor function at an early stage is crucial to the life of the patient. Objectives. To invest the effects of additional mirror therapy in improving upper limb motor function and activities of daily living in acute and subacute stroke patients, and further explore the effects of other factors on the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
2
5
0
5
Order By: Relevance
“…Furthermore, significant and highly significant differences were observed between the CG and the two EG, indicating a superior improvement for both EG compared to the CG, except for the range of motion and pain domain. These results are consistent with other studies suggesting that groups incorporating MT and cognitive exercises show greater motor and functional recovery and better self-care compared to CG [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, significant and highly significant differences were observed between the CG and the two EG, indicating a superior improvement for both EG compared to the CG, except for the range of motion and pain domain. These results are consistent with other studies suggesting that groups incorporating MT and cognitive exercises show greater motor and functional recovery and better self-care compared to CG [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…The statistically significant differences in global limb functionality, motor domain and sensory domain are consistent, with several studies indicating that intervention using MT and CTE improves the total FMA-EU score, thus increasing upper limb functionality and motor domain, which in turn improves motor function and ADLs [39,40].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kegiatan setiap hari lebih banyak atau tergantung bantuan orang lain . Dalam artikel (Wen et al, 2022) perawatan yang diperlukan setiap pasien stroke bisa mungkin berbeda dengan pasien yang lainnya. Hal ini tergantung pada kebutuhan dan gejala pasien stroke.…”
Section: Pembahasanunclassified
“…8 Early exercise interventions are necessary to improve upper extremity motor functions and activities of daily living (ADL), as persistent upper extremity dysfunction is strongly associated with decreased activities of daily living and poor quality of life after stroke. [9][10][11] Occupational therapy (OT) is a part of medical rehabilitation therapy aimed at restoring, strengthening and increasing the person's performance in specified activities and tasks in order to improve health, reduce and correct pathology. 4 Studies have shown that OT shortens the length of hospital stay, increases activities of daily living, and increases the level of independence in stroke patients.…”
Section: Introductionmentioning
confidence: 99%